Analysis of the nicotinamide phosphoribosyltransferase family provides insight into vertebrate adaptation to different oxygen levels during the water‐to‐land transition. (16th June 2015) - Fang, Chengchi; Guan, Lihong; Zhong, Zaixuan; Gan, Xiaoni; He, Shunping
<x xml:space="preserve">Abstract</x> One of the most important events in vertebrate evolutionary history is the water‐to‐land transition, during which some morphological and physiological changes occurred in concert with the loss of specific genes in tetrapods. However, the molecular mechanisms underlying this transition have not been well explored. To explore vertebrate adaptation to different oxygen levels during the water‐to‐land transition, we performed comprehensive bioinformatics and experimental analysis aiming to investigate the NAMPT family in vertebrates. NAMPT, a rate‐limiting enzyme in the salvage pathway of NAD+ biosynthesis, is critical for cell survival in a hypoxic environment, and a high level of NAMPT significantly augments oxidative stress in normoxic environments. Phylogenetic analysis showed that NAMPT duplicates arose from a second round whole‐genome duplication event. NAMPTA existed in all classes of vertebrates, whereas NAMPTB was only found in fishes and not tetrapods. Asymmetric evolutionary rates and purifying selection were the main evolutionary forces involved. Although functional analysis identified several functionally divergent sites during NAMPT family evolution, in vitro experimental data demonstrated that NAMPTA and NAMPTB were functionally conserved for NAMPT enzymatic function in the NAD+ salvage pathway. In situ hybridization revealed broad NAMPTA and NAMPTB expression patterns, implying regulatory functions over a wide range of developmental processes. The morpholino‐mediated knockdown data demonstrated that NAMPTA was more essential than NAMPTB for vertebrate embryo development. We propose that the retention of NAMPTB in water‐breathing fishes and its loss in air‐breathing tetrapods resulted from vertebrate adaptation to different oxygen levels during the water‐to‐land transition.